2021
DOI: 10.1002/nop2.1153
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of COVID‐19 pandemic‐related organizational aspects in health care

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This makes it possible to move staff (voluntary or imposed) from other departments of the hospital. Previous studies have reported staff movements within the hospital, such as physicians and nurses from different specialties assisting in the ICU, ED, and inpatient care units [ 7 , 21 , 24 , 27 ]. In the Netherlands, 61% of the EDs were expanded with nursing staff and physicians from other departments for COVID-19 emergency care [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…This makes it possible to move staff (voluntary or imposed) from other departments of the hospital. Previous studies have reported staff movements within the hospital, such as physicians and nurses from different specialties assisting in the ICU, ED, and inpatient care units [ 7 , 21 , 24 , 27 ]. In the Netherlands, 61% of the EDs were expanded with nursing staff and physicians from other departments for COVID-19 emergency care [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, anesthesiologists could knowledgeably contribute to the ICU requirements [ 20 ]. However, Jensen et al [ 27 ] have reported that many of the healthcare workers who had moved perceived that their new job did not resemble their usual job at all, or only resembled it to a small degree. Consequently, the staff in the new positions needed rapid training.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations